Estudo da deterioração da celulose por tratamentos de conservação e interações com a tinta ferrogálica - Matheus de Castro e Silva (2015)
This work studied interactions between cellulose and several substances widely used in conservation and restoration of cultural heritage. In order to study the deterioration of cellulose by the treatments effects, paper prototypes were produced with Whatman No. 1. The papers were submerged in solutions used in conservation and restoration treatments, such as gallic acid and some of its derivatives solutions, then its acidity was measured, after drying, by three different methods of pH. The acidity of the samples was evaluated again after a soft artificial aging by light, to verify a possible relationship between acidity and deterioration of the prototypes. The papers exposed to treatments with organic acids or salts with a high content of metal obtained the lowest pH values after aging. The deterioration of the prototypes was evaluated by thermal analysis of cellulosic support, comparing the reference treated with prototypes by three techniques: TG, DTA and DTG, before and after aging. The findings show that substances such as sodium hypochlorite, aluminum and potassium sulfate contributed to the degradation of cellulosic polymer. Based on pH data and thermal analysis curves, it was observed that the pH is a limited indicator of the cellulose support condition. In the third part of this work, the study of the interaction between iron ions with gallic acid and gum arabic - main constituents of iron gall ink - was done by absorption spectroscopy in the ultraviolet and visible region (UV-vis). It is observed that the reactions involving such compounds have great complexity and they become diferent according to the ratio between the gallic acid and iron ions, pH and stabilization provided by other reagents added to the system. The analysis of the spectra relating to iron gall ink produced in the presence of gelatin demonstrates a complex formed from the interaction of the protein chain, stabilizing the formed species and intensified color ink.